Influence of key community leaders to enhance the tuberculosis awareness in the community: A mixed-method study - Reenaa Mohan; Kalaiselvan Ganapathy (Journal of Clinical and Scientific Research, 2025)
Background: Training community leaders about tuberculosis (TB) is considered to facilitate increased awareness in the community about TB. We studied the knowledge gap about TB and assessed the knowledge of key community leaders (KCL) about TB before and after interventions. Methods: Community-based mixed-method study which includes qualitative method and before and after study. In the qualitative method: key informant interview (KII) was conducted with stakeholders who were selected based on homogeneous purposive sampling to identify the key message (TB knowledge gap in the community) to prepare health education tools and provide focused intervention. In quantitative method (survey using questionnaire) was done with KCL from diverse sectors were selected through snowball sampling. The study was carried out for 15 months in the 14 villages, field practice area of primary health centre. Results: From key informant interview, the stakeholders stated community people awareness regarding health-seeking behaviour of TB is poor. The mean age (years) of KCL (n = 117) was 44.6 ± 10; majority (64%) were females. Knowledge regarding comorbid conditions more prone to TB, the role of alcohol/smoking in TB and extrapulmonary TB were not statistically significant. Conclusions: Leaders from diverse backgrounds were involved in the study, which helped in community participation on TB.